2016
DOI: 10.4172/2150-3494.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Nay Zeolite from Rice Husk Silica: Modification with Zno and Zns for Antibacterial Application

Abstract: Zeolite Y in the sodium form (NaY) was synthesized using amorphous silica ash derived from waste rice husks under hydrothermal conditions. Structural characterization of NaY before and after modification with ZnO and ZnS has been done using powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), N 2 adsorption-desorption at -196 °C, scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. The effects of the Na 2 O/SiO 2 and Si/Al ratios, aging temperature and cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Gram-positive bacteria have a thick peptidoglycan layer with complex cell walls, so Yzeolite is not easily absorbed into bacterial cells. This causes gram-positive bacteria to be more resistant to antibacterial agents 37 .…”
Section: Antibacterial Activity Testmentioning
confidence: 99%
“…Gram-positive bacteria have a thick peptidoglycan layer with complex cell walls, so Yzeolite is not easily absorbed into bacterial cells. This causes gram-positive bacteria to be more resistant to antibacterial agents 37 .…”
Section: Antibacterial Activity Testmentioning
confidence: 99%
“…Zinc oxide is of particular interest due to their comparably modest cost and their established use in health care products [26]. Recently, several studies have demonstrated quite efficient antimicrobial activity of zinc Oxide nano particles against gram-positive and gram-negative bacteria [27,28]. Several attempts to design various silver/ zinc oxide nanocomposites with an antibacterial activity against gram positive and gram-negative bacteria have been introduced in the literature [29,30].…”
Section: Introductionmentioning
confidence: 99%